2022
DOI: 10.1021/acs.chemmater.2c03224
|View full text |Cite
|
Sign up to set email alerts
|

Probing Local Structural Changes by Sharp Luminescent Infrared Nanophosphor for Application in Light-Emitting Diodes

Abstract: Cr3+-doped infrared phosphors are promising candidates for next-generation phosphor-converted infrared light-emitting diodes (LEDs) because they can, in principle, tune and convert the luminescence spectra from an LED chip. However, most studies focus on broad-band Cr3+-doped phosphors, and the control mechanism of Cr3+-doped phosphors with sharp line emissions remains ambiguous. Here, we report LiGa5(1–x)Al5x O8:Cr3+ phosphors with sharp line emissions. The luminescence analysis reveals the subtle change of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…In our earlier study, we also demonstrated that in LiAl 5 O 8 , as the homeotypic structure of LiGa 5 O 8 , part of the Li occupies the Al octahedral site, and part of the Al occupies the Li sites, proving the possibility of the partial‐inverse occupation. [ 6 ] Similar perspective is also provided by Khaidukov et al. in the LiAl 5 O 8 :Cr 3+ system.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…In our earlier study, we also demonstrated that in LiAl 5 O 8 , as the homeotypic structure of LiGa 5 O 8 , part of the Li occupies the Al octahedral site, and part of the Al occupies the Li sites, proving the possibility of the partial‐inverse occupation. [ 6 ] Similar perspective is also provided by Khaidukov et al. in the LiAl 5 O 8 :Cr 3+ system.…”
Section: Resultssupporting
confidence: 57%
“…In our earlier study, we also demonstrated that in LiAl 5 O 8 , as the homeotypic structure of LiGa 5 O 8 , part of the Li occupies the Al octahedral site, and part of the Al occupies the Li sites, proving the possibility of the partial-inverse occupation. [6] Similar perspective is also provided by Khaidukov et al in the LiAl 5 O 8 :Cr 3+ system. [5a] With the similar ionic radii between Ga 3+ and Cr 3+ , this partial-inverse occupation may also happen at high Cr concentrations, leading to an unexpected Cr2 emission (Figure 3b) and broadening of the Raman peaks (Figure S3, Supporting Information).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The calculated lattice distortion index D values of [CaO 8 ] exhibited an increase from 1.41 to 2.32% in Table S2b (ESI†). 38–41 This proves our inference that the doping of Ce 3+ distorts the [CaO 8 ] dodecahedron and improves the d–d forbidden transition, which leads to a continuous increase in the NIR emission intensity under 480 nm excitation. The IQE of CSGG:0.14Cr 3+ ,0.16Ce 3+ is measured to be 61% under 480 nm excitation, which is nearly 3 times higher than that of CSGG:0.14Cr 3+ without Ce 3+ (IQE = 22%).…”
Section: Resultssupporting
confidence: 73%
“…After pressure is used, the shrinkage of the crystal lattice decreases the distance between Cr 3+ ions forming the ion pair, and the strength of the interaction increases. The stronger interaction between Cr 3+ ions in a pair will result in a greater distance from the Cr 3+ –Cr 3+ luminescence to the R-line of isolated Cr 3+ . The applied pressure shifts Ni 2+ emission linearly toward higher energies at a rate of 100 ± 10 cm –1 /GPa ( x = 0.02 + H 3 BO 3 flux) and 104 ± 4 cm –1 /GPa ( x = 0.02) due to the pressure-induced increase of the crystal field strength.…”
mentioning
confidence: 99%